Utilizing APACHE IV and GRACE Scores as Predictors of Mortality Compared with SAPS-3 Scores for Acute Coronary Syndrome Patients in the Cardiac Vascular Care Unit - Nugraha, Tria Yudha; Prasetya, Indra; Anjarwani, Setyasih (Heart Science Journal, 2024)
Background: Acute coronary syndromes (ACS) frequent cause of hospitalization in the cardiovascular care unit. Positive predictive data are being developed and shown to be effective for patients with ACS; the Global Registry of Acute Coronary Events, or GRACE, has shown the most accurate outcomes. In contrast, prognostic scores derived from diverse cohorts of critically ill patients are predominantly employed by intensive care clinicians. Prominent examples of such scores include APACHE IV and SAPS 3. The objective of this research endeavor was to assess and contrast the efficacy of these three scores across an unselected sample of ACS cases.Objective: The Cardiovascular Care Unit of RSUD Dr. Saiful Anwar Malang treats Acute Coronary Syndrome patients. This study compares SAPS 3, GRACE, and APACHE IV score parameters through calibration and discrimination tests to predict patient mortality.Methods: The study included all ACS patients admitted from August 2021 to November 2023. Hospital mortality prediction was assessed using score calibration and discrimination.Results: There were 843 patients in total included. SAPS 3 could not be calibrated appropriately, whereas APACHE IV and GRACE could. Across all scores, discrimination was exceptional (area under the curve values of 0.811 for APACHE IV, 0.740 for GRACE, and 0.732 for SAPS 3).Conclusions: GRACE and APACHE IV were calibrated thoroughly in this cohort of intensive care unit-admitted ACS patients; however, SAPS 3 lacked such calibration. All three scores exhibited exceptional discrimination. GRACE and APACHE IV may be utilized to predict the risk of mortality in patients with ACS.